Penerapan Kajian Kitab Ta’lim Muta’allim dalam Pembentukan Akhlak Siswa di MA Tarbiyatul Banin Banat Jetak-Montong Tuban - Mubaidilla, Irfa'i Alfian; Cholifah; Sholihin, Thobi’us; Anwarrudin, Thoiful; Ma’sumah, Siti (Tarunaedu: Journal of Education and Learning, 2024)
This research is motivated by the application of the study of the Ta'lim Muta'alim book in private educational institutions in the formation of student morals at MA Tarbiyatul Banin Banat and the application of this study with regular learning to support school programs. This research aims to determine the application of the study of the Ta'lim Muta'alim book in the formation of student morals at MA Tarbiyatul Banin Banat and to determine the supporting and inhibiting factors. This research uses a qualitative descriptive approach with field research. The informant for this research is a teacher studying the book Ta'lim Muta'alim. The data collection techniques were obtained through observation, interviews, and documentation. Meanwhile, data analysis uses data reduction, data presentation, and verification. Based on the results of the research, it can be concluded that: 1) planning was carried out by reading Asmaul Husna and continued with the presentation of the contents of the book Ta'lim Muta'alim. Furthermore, all students take part in the book study every day after completing Monday's ceremony and morning assembly, with a duration of 20-30 minutes. Lastly, there was an evaluation based on the results of observations of the majority of students who had seenchanges in their morals, such as their confidence and awareness of carrying out worship as an obligation, towards teachers being more respectful when walking in front of them, bowing their bodies, saying hello when they met, and having good manners and character towards friends. . However, there are also some students who still do not apply these morals according to those in the Ta'lim Muta'alim book, especially towards teachers because they don't like to always be ordered and are often late when coming toschool. It is not only a change in morals but also an increase in knowledge about the contents of the book Ta'lim Muta'alim because, after completing the study of the book, the study teacher will ask questions to students regarding what things were obtained when carrying out the study of the book Ta'lim Muta'alim. 2) Supporting and inhibiting factors: for supporting factors, there is he ability and willingness of study teachers; the majority of students are enthusiastic about participating in the study ofthe book; the environment is beautiful or cool; and the school facilities are quite adequate. Meanwhile, the inhibiting factors are still a lack of study teams or teachers, students who feel tired or fed up, power outages, and a damaged sound system.